ISLAMIC PERSPECTIVES ON ENVIRONMENTAL TAX: A REVIEW OF LITERATURE - Muhammad, Izlawanie (I-iECONS e-proceedings, 2023)
Allah makes this earth a shared place for humans and other living creatures, including water, air and soil, to grow, harness and interact. As the superior creation, humans play significant roles in protecting the earth from destruction, ensuring its sustainability and necessitating it as a safe place for future generations. Indeed, poor human behaviours and awareness of preserving the earth have caused countless negative environmental impacts (e.g. landslides, floods, bushfires, haze, deforestation, pollution), and climate changes warrant laws and punitive controls. Many Muslim countries have introduced environmental tax as one of the tools to punish polluters and change their behaviour. While Islam allows tax to be collected by the government to develop a country, little is known in the context of environmental tax. This paper aims to analyse the Islamic perspectives on environmental taxes. A qualitative research methodology was adopted by thematic analysis of published books, articles and research papers. The analysis shows that while there are numerous research articles on Islam and the environment, only one empirical study (Al-Rawi et al., 2022) examines the Islamic perspectives on environmental tax. The study found that Islamic scholars have different opinions about environmental tax. Those on the supporting side explain that the environment considers a penalty or fine for causing damage to society, which makes it justifiable in Islam. However, the implementation must be carefully designed to ensure fairness and avoid unnecessary burdens to the public. More research should be undertaken to gather more opinions from the experts and compare other types of taxes permissible in Islam.